Welfare states as lifecycle redistribution machines: Decomposing the roles of age and socio-economic status shows that European tax-and-benefit systems primarily redistribute across age groups - Vanhuysse, Pieter; Medgyesi, Marton; Gal, Robert I. (PLOS ONE, 2021)
Social scientists identify two core functions of modern welfare states as redistribution across (a) socio-economic status groups (Robin Hood) and (b) ‘the lifecycle’ (the piggy bank). But what is the relative importance of these functions? The answer has been elusive, as the piggy bank is metaphorical. The intra-personal time-travel of resources it implies is based on non-quid-pro-quo transfers. In practice, ‘lifecycle redistribution’ must operate through inter-age-group resource reallocation in cross-section. Since at any time different birth cohorts live together, ‘resource-productive’ working-aged people are taxed to finance consumption of ‘resource-dependent’ younger and older people. In a novel decomposition analysis, we study the joint distribution of socio-economic status, age, and respectively (a) all cash and in-kind transfers (‘benefits’), (b) financing contributions (‘taxes’), and (c) resulting ‘net benefits,’ on a sample of over 400,000 Europeans from 22 EU countries. European welfare states, often maligned as ineffective Robin Hood vehicles riddled with Matthew effects, are better characterized as inter-age redistribution machines performing a more important second task rather well: lifecycle consumption smoothing. Social policies serve multiple goals in Europe, but empirically they are neither primarily nor solely responsible for poverty relief and inequality reduction.